ANALYSIS OF FFT AND DWT BASED OFDM (International Journal of Engineering and Computer Science, 2014)
This paper examines the performance of Discrete Wavelet Transform based OFDM (DWT-OFDM) and Fast Fourier based OFDM (FFT-OFDM) system. A new interleaving scheme is applied to system for efficient data transmission over AWGN channel. The performance of the approach is evaluated on the DWT-OFDM and FFT-OFDM with interfacing and without interleaving process. Signal to Noise ratio (SNR) and Bit Error Rate (BER) is used as system parameter to evaluate the performance of the OFDM system. The simulation result of new interleaving scheme using  PN sequence generator and different gain input  gives better bit error rate of DWT based OFDM system